2001
DOI: 10.1039/b004532m
|View full text |Cite
|
Sign up to set email alerts
|

Response mechanism of a neutral carrier Hg(ii) polymeric membrane ion-selective electrode. SEM and EDAX study

Abstract: Scanning electron microscopy (SEM) and energy dispersive atomic X-ray spectrometry (EDAX) were used to study the response mechanism of a previously reported new Hg membrane ion-selective electrode (ISE) based on 1,3-diphenylthiourea. These techniques allowed the study of the membrane surface characteristics, such as the morphological homogeneity and chemical composition. A 'twice Nernstian' response at pH > or = 7 was explained by the detection of the Hg(OH)+ cation. A normal Nernstian response was found at ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Therefore, F3DET is responsible for the selectivity of the ISE to Cd (II) cation. The relation metal/ionophore was determined by chemical microanalysis The results showed that for M2 and M3 the Cd/S relation was 1:1 which corresponds to that reported in the literature for ISE containing a neutral carrier 11 .…”
supporting
confidence: 66%
“…Therefore, F3DET is responsible for the selectivity of the ISE to Cd (II) cation. The relation metal/ionophore was determined by chemical microanalysis The results showed that for M2 and M3 the Cd/S relation was 1:1 which corresponds to that reported in the literature for ISE containing a neutral carrier 11 .…”
supporting
confidence: 66%
“…Test solutions were at an ionic strength of 0.1 M maintained by sodium nitrate and the pH value of the solutions was maintained at 6 with PIPES buffer 0.01 M. Before each set of measurements, the electrode surface was renovated and the ISE was introduced in 0.1 M NaNO 3 and 0.01 M PIPES solution during 15 ± 20 minutes to obtain steady potential measurements. The addition method was used as a standard technique for evaluating the electrode response characteristics [32,33]. The additions were made with micropipettes, keeping the tip of the micropipettes just above the surface of solutions while making the addition [18].…”
Section: Emf Measurementsmentioning
confidence: 99%
“…The construction of sensitive and correct appliances based on electrochemical sensors, capable of quantifying and detecting the concentration of contaminating substances in different ecosystems has been the subject of growing significance in recent years (Malinowska et al, 2000;Pineros et al, 1998;Perez-Marin et al, 2001;Arada Perez et al, 2003). Because ion selective electrodes show good selectivity for different ions, so they are very suitable for measuring the content of the considered ions.…”
Section: Introductionmentioning
confidence: 99%